Polymerisation of 2-acrylamido-2-methylpropane sulfonic acid sodium salt (NaAMPS) and acryloyl phosphatidylcholine (APC) via aqueous Cu(0)-mediated radical polymerisation. Issue 14 (22nd March 2016) - Nikolaou, Vasiliki; Simula, Alexandre; Droesbeke, Martijn; Risangud, Nuttapol; Anastasaki, Athina; Kempe, Kristian; Wilson, Paul; Haddleton, David M.
Abstract : The scope of aqueous Cu(0)-mediated living radical polymerisation has been expanded with the preparation of poly(2-acrylamido-2-methylpropane sulfonic acid)sodium salt (P(NaAMPS)) and poly(acryloyl phosphatidycholine) (PAPC). Abstract : The scope of aqueous Cu(0)-mediated living radical polymerisation has been expanded with the preparation of poly(2-acrylamido-2-methylpropane sulfonic acid)sodium salt (P(NaAMPS)) and poly(acryloyl phosphatidycholine) (PAPC). Manipulation of the reaction conditions furnishes polymers capable of undergoing chain extension and supporting the synthesis of block copolymers at 0 °C.